MEASURING THE DOMINANT PARADIGMA IN UNITED NATIONS CONVENTION ON THE LAW OF THE SEA - Nadhif Fadhlan Musyaffa; Arie Kusuma Paksi; Lalu Radi Myarta (Lampung Journal of International Law, 2022)
This study discusses the paradigm used by the United Nations in governing relations among countries on sea-related issues through the analysis of the United Nations Convention on the Law of the Sea. Laws/regulations on sea-related issues have undergone changes, since their inception in 1958 in line with the development of the issue of sea between countries and the factors that cause the proliferation of sea-related disputes, as well as political and economic dynamics in the international sphere. Reforms in the regulatory mechanism on sea-related issues between countries by the United Nations were marked by the formation of the United Nations Convention on the Law of the Sea in 1982 which has several stipulations. This writing aims to analyze and measure the paradigm used by the United Nations in regulating mechanisms on sea-related issues between countries through the analysis of the United Nations Convention on the Law of the Sea. The author uses the content analysis method in analyzing the law. The analysis was carried out on three indicators; actors, authorities, and governance representing the three paradigms; realism (competition), liberalism (collaboration), and constructivism (historical and social construction). Based on the analysis results, it can be concluded that; the United Nations Convention on the Law of the Sea concerning the regulation mechanism on sea-related issues between countries is strongly influenced by the realism paradigm.